2015
DOI: 10.1007/s00203-015-1169-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of exopolysaccharides biosynthesis gene clusters in Lactobacillus plantarum

Abstract: Exopolysaccharides (EPS) from lactic acid bacteria contribute to specific rheology and texture of fermented milk products and find applications also in non-dairy foods and in therapeutics. Recently, four clusters of genes (cps) associated with surface polysaccharide production have been identified in Lactobacillus plantarum WCFS1, a probiotic and food-associated lactobacillus. These clusters are involved in cell surface architecture and probably in release and/or exposure of immunomodulating bacterial molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The EPS produced by the mutant Δ cps1A-J genes has modified the molecular weight and lacks rhamnose, whereas mutations in the other three individual cluster deletions, or the quadruple-deletion, resulted in a reduction of the amount of polymer synthesised. Later, by means of transcriptional analysis it was found that the four cps loci of WCFS1 were organized in five operons, three of them under the control of the global regulator CcpA [ 46 ]. It is worth noting that L. plantarum WCFS1 does not have a ropy phenotype, which was present in the strains SF2A35B and Lp90 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The EPS produced by the mutant Δ cps1A-J genes has modified the molecular weight and lacks rhamnose, whereas mutations in the other three individual cluster deletions, or the quadruple-deletion, resulted in a reduction of the amount of polymer synthesised. Later, by means of transcriptional analysis it was found that the four cps loci of WCFS1 were organized in five operons, three of them under the control of the global regulator CcpA [ 46 ]. It is worth noting that L. plantarum WCFS1 does not have a ropy phenotype, which was present in the strains SF2A35B and Lp90 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthesis of the former requires fewer enzymes, whereas that of the latter occurring via the Wzy-dependent pathway is conferred by gene clusters encoding the enzymes and other proteins involved in the assembly and transport of these polymers as well as the regulation of this process [25]. Gene organization and functional properties of the EPS gene clusters have been studied in some lactobacilli, such as L. delbreuckii [4], L. helveticus [26], L. johnsonii [8,10,27], L. paraplantarum [28], L. plantarum [29,30,31] and L. rhamnosus [6,32]. These studies have highlighted some common features of EPS gene clusters in Lactobacillus such as the presence of the regulatory genes on the 5’end, polymerization and export-related genes on the 3’end and glycosyltransferase (gt) genes at the center of the cluster (reviewed by Zeidan et al, 2017) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Many differences in the EPS gene clusters of various species are also reported. Some species such as L. johnsonii and L. helveticus harbor a single cluster [8,10,26,27], whereas few species such as L. plantarum and L. paraplantarum have multiple clusters [28,29,30,31]. At the 5’end, the first five genes of the clusters including a transcriptional regulator, epsA ; a phosphoregulatory module, epsBCD ; and a priming glycosyltransferase, epsE are usually conserved and present in a specific order often referred to as epsABCDE stretch in generic EPS clusters [8,10,24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…L. mucosae DPC6426 [2][3][4]10] and LM1 [6] were reported to generate EPS significantly, but the EPS gene cluster was not explored in depth. Genomic studies on lactic acid bacteria indicated that the biosynthetic pathway of EPS was controlled by several housekeeping genes and a series of EPS-related genes that were involved in regulating EPS production, chain-length, biosynthesis of repeating units, and aggregation and export of repeating unit [53][54][55][56]. In the current work, it was found that 82% of the strains lacked the chain length-determining protein, and it was speculated that these strains lost the ability to synthesize EPS.…”
Section: Discussionmentioning
confidence: 68%
“…It was worth noting that the third putative protein of the EPS gene cluster in some strains was missing. However, since the contribution of the hypothetical protein was not significant, it did not affect the synthesis of EPS [55]. Although discussion of EPS was still open, the fact that EPS clusters in L. mucosae has little change in the presence of particular genes should be highlighted.…”
Section: Discussionmentioning
confidence: 99%